GALECTIN-3 AS A MARKER OF MYOCARDIAL FUNCTION IN MEN AGED 40-60 YEARS WITHOUT CARDIOVASCULAR PATHOLOGY, CARRIERS OF POLYMORPHIC GENES AT1R - V.O. Ruzhanska; V.G. Sivak; M.S. Lozinska; V.М. Zhebel (Проблеми екології та медицини)
The concentrations of galectin-3 and BNP, central and systemic hemodynamics, structural and functional heart parameters in male carriers of polymorphic AT1R genes without cardiovascular pathology (n = 79) living in Podillya region were studied. Genotyping of the AT1R gene was carried out using a polymerase chain reaction. The level of galectin-3 and BNP was determined by the method of enzyme immunoassay. It was found that the A1166A genotype dominated in practically healthy men of Podilly region. Nevertheless, the level of galectin-3 and BNP in the studied population did not significantly depend on the carriage of a specific variant of the AT1R gene.